Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Konsumen Pada CV Smart Quality Technic Curug Bojongsari Kota Depok - Alvin Adam Saputra; Aris Ariyanto (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine the effect of service quality and price on consumer satisfaction at CV. Smart Quality Technic Curug Bojongsari, Depok City. The method used is a quantitative associative method. The population in this study were consumers of CV. Smart Quality Technic Curug Bojongsari, Depok City. The sampling technique used was accidental sampling, the sampling method using the Slovin formula. With the Slovin formula, the research sample was 96 respondents. Data analysis methods used in the study include instrument tests consisting of validity tests, reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity and autocorrelation tests, multiple linear regression tests, correlation coefficients, hypothesis tests consisting of partial t-tests and simultaneous f-tests, and determination coefficient tests. From the results of this study, it was concluded that service quality has a positive and significant influence on consumer satisfaction with a calculated T value > T table (15.070 > 1.986) and strengthened by a significance value of 0.000 < 0.05. Price has a positive and significant influence on consumer satisfaction with a value of T_count > T_table or (17.865> 1.986) and is strengthened by a significance value of 0.000 <0.05. Service quality and price have a positive and significant influence on consumer satisfaction with a value of F_count > F_table or (188.151> 3.090) and is strengthened by a significance value of 0.000 <0.05. Service quality and work price on consumer satisfaction have a regression effect of Y = 4.511 + 0.333 X1 + 0.550 X2 + α. The results of the R-square value (coefficient of determination) of 0.802, it can be concluded that the variables of service quality (X1) and price (X2) together have a contribution to the influence of the consumer satisfaction variable (Y) of 80.2% while the remaining (100% -80.2%) is 19.8% influenced by other factors or variables not studied.